ANALYSIS OF LEADING SECTORS IN SOUTH TANGERANG FOR DETERMINING REGIONAL DEVELOPMENT PRIORITIES - Sutanti, Sutanti; Oktariani, Dwi (Muhammadiyah University Press, 2019)
A sustainable economic growth becomes a main requirement for the continuity of regional economic development. Therefore, it should be concentrated on the basic sectors or leading sectors in order to create significant multiplier effect on other sectors. It is urgency for newly established regions, e.g., South Tangerang. This study aims to determine and analyze leading sectors that possess competitiveness and specialization in South Tangerang in relation with the future economic growth of South Tangerang. In addition, it also aims to project the added value or GRDP of South Tangerang in 2017. Secondary data in the form of time series sectoral GRDP at constant prices of both South Tangerang and Banten from 2010 to 2016 were obtained from BPS South Tangerang City and BPS of Banten Province. The data were analyzed using a quantitative- descriptive approach through the Location Quotient (LQ) and Shift-Share analysis. Based on the LQ method, there are nine leading sectors in 2010?2016, namely: construction; wholesale and retail trade, and repair of motor vehicles and motorcycles; accommodation and food; information and communication; real estate; corporate services; educational services; health and social services; and other services. The average LQ for these sectors is, respectively, 1.490; 1.333;1.315; 2.969; 2.233; 3.299; 2.530; 3.663; and 2.014. Real estate has the highest values, indicating it becomes the leading sector with the highest competitive and comparative advantages.